Dyslipidemia and associated factors among hypertensive patients in Ethiopia: a systematic review and meta-analysis - Worku Chekol Tassew; Samson Sisay Woldie; Yeshiwas Ayale Ferede; Agerie Mengistie Zeleke; Adane Nigussie (BMC Cardiovascular Disorders)
Abstract Introduction Dyslipidemia and other CVD risk factors in cardiac patients can lead to accelerated atherosclerosis, morbidity, and significant mortality. Identifying the potential contributory factors of dyslipidemia in hypertensive patients is crucial in order to manage the disease condition and reduce further complications. Although dyslipidemia has been studied in many countries, evidence of pooled prevalence and its risk factors in Ethiopia remains scarce. Thus, this meta-analysis aimed to estimate the pooled prevalence of dyslipidemia (high TG, low HDL-C, high LDL-C, and high TC) and associated factors among adults with hypertension in Ethiopia. Methods The reporting system adhered to the Preferred Reporting Items for Systematic Review and Meta-analysis guidelines. Articles were searched using electronic databases such as PubMed, Cochrane Library, Science Direct, African Journals Online, and Google Scholar from April 1 to April 21, 2024 to find relevant studies. We utilized Endnote X7 and STATA 11 for bibliographical management and statistical analysis, respectively. The heterogeneity of the included studies was analyzed using forest plots, Cochran’s Q statistics, I² test, and P-values. Results The electronic searches yielded 10,629 articles. Based on the quality assessment, all the included studies had high quality. The overall pooled prevalence of dyslipidemia among hypertensive patients in Ethiopia was 37.12% (95% CI: 31.79–42.44%; I²=98.4%). The pooled point estimates for high TC were (33.39%, 95% CI: 23.92–42.85; I²=97.9%), TG (38.89%, 95% CI: 32.90–44.88; I²=93.6%), high LDL-c (33.98%, 95% CI: 21.46–46.49; I²=98.4%), and low HDL-c (42.23%, 95% CI: 28.76–55.71; I²=98.9%). Based on this meta-analysis, dyslipidemia was associated with age ≥ 40 years and sedentary lifestyle. Conclusion This study suggests that dyslipidemia was high among the study participants, which underlines urgent need for early detection and public health interventions through the integrated involvement of public, governmental, and non-governmental organizations. Dyslipidemia was associated with, age ≥ 40 years, and sedentary lifestyle. This alarms the need for lipid profile assessment for patients periodically, with treatment follow-up to monitor any rising patterns and cardiovascular related risks.